Correction: The Type of Bariatric Surgery Impacts the Risk of Acute Pancreatitis: A Nationwide Study. Issue 10 (October 2018) - Hussan, Hisham; Ugbarugba, Emmanuel; Porter, Kyle; Noria, Sabrena; Needleman, Bradley; Clinton, Steven; Conwell, Darwin; Krishna, Somashekar
In the original version of this Article, a footnote was missing. The PDF and HTML versions of the Article have now been corrected to include the following: This study was presented as an abstract at the World Congress of Gastroenterology (WCOG) at ACG 2017, Orlando Florida.